Observations on coastal marine water circulation in the zone Midia - Vama Veche - Nae, Ion; Postolache, Iulian (Cercetări Marine - Recherches Marines, 2026)
Analysis is carried out on currents measurements from 12 to 24 stations located along the coast at 5 and 10m depths between Midia and Vama Veche, in the period 1972-1978 on about 4000 records obtained from self-recording currentmeters of the Alexeyev type in the bay of Mamaia; daily observations (three times every day) in the roads of the port of Constanta in 1979. The results were presented as arranged on type of resultant circulation in the four cardinal directions.